PERGESERAN NILAI SIKAP UNGGAH UNGGUH PADA MASYARAKAT JAWA DI DESA ENGGAL REJO JALUR AIR SALEK - Arif Sarifudin; Baldi Anggara; Husnah Lutfiah; Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
This study aims to determine the values ​​of uploading ungguh attitudes in Javanese society in Enggal Rejo Village and to describe what factors affect the erosion of the values ​​of the uploading attitude in society Javanese people in Enggal Rejo Village. This research is a phenomenological research with a qualitative approach. The subjects of this study were teenagers and parents of Javanese descent living in Enggal Rejo Village and collecting research data through three primary sources: direct observation (observation), document analysis, and in-depth interviews. To improve the accuracy of the data, the researchers used triangulation and data analysis using the interactive analysis technique of the Miles and Huberman model. The results of this study are: (1) The form of the value of the upload-ungguh attitude in the Javanese community in the Enggal Rejo Village, Jalan Air Salek is to maintain politeness in behavior, maintain the Javanese language in communication, continue to get used to mutual cooperation activities, and respect older people in communicating. say hello; and (2) the factors that influence the shift in the value of uploading-ungguh among adolescents in enggal Rejo village are environmental factors, associations, the area occupied, understanding of parents, and a sense of love for the value of upload-ungguh attitude itself.